2018
DOI: 10.18203/2394-6040.ijcmph20184207
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess unmet need for family planning and contraceptive choices among married women of reproductive age in rural Madhya Pradesh

Abstract: Background: The unmet need of family planning refers to the gap between reproduction intention of a couple and their contraceptive behavior. According to NFHS-4 the unmet need for family planning is 12.9 in India. The objectives of the study were to assess the unmet need for family planning and to find out the contraceptive choices among married women.Methods: This cross sectional study was undertaken in the rural field practice area of Department of Community Medicine, Index Medical College, Indore, from Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…A study done by Sahasrabuddhe et al, found that unmet need for family planning was 23%, which was in contrast to our study. 11 Our study findings corroborated with NFHS-4 survey, that found 13 % of currently married women have an unmet need for family planning. If all currently married women who want to space or limit their children were to use a family planning method, the contraceptive prevalence rate would increase from 54 % to 66 %.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study done by Sahasrabuddhe et al, found that unmet need for family planning was 23%, which was in contrast to our study. 11 Our study findings corroborated with NFHS-4 survey, that found 13 % of currently married women have an unmet need for family planning. If all currently married women who want to space or limit their children were to use a family planning method, the contraceptive prevalence rate would increase from 54 % to 66 %.…”
Section: Discussionsupporting
confidence: 89%
“…The findings nearly corroborated with that of the study conducted in rural Madhya Pradesh , where it was found that 70.9% were using contraceptives, with female sterilization being the most common method preferred (36%), followed by male condoms (6%) and pills (4%). 11 As per NFHS 4 survey, 99% of currently married women aged 15-49 knew at least one method of contraception. Overall, the contraceptive prevalence rate (CPR) was found to be 54% among currently married women (15-49 years).…”
Section: Discussionmentioning
confidence: 99%
“…19 Sahasrabuddhe et al reported family interference, cultural as well as religious restrictions followed by health concern and fear of permanent loss of fertility as primary reasons for lesser acceptance and usage of family planning measures. 20 The current study results show that Knowledge levels of the subjects were found to have significant association with Religion, Occupation and Use of contraceptives. A study conducted by Mathew et al and Sharma et al reported statistically significant association of knowledge regarding family planning measures with age, education, occupation, number of living children and current use of family planning methods.…”
Section: Discussionmentioning
confidence: 48%
“…This might imply that there is little out-of-pocket payment because family planning service has been incorporated into the national health insurance scheme since 2014. The premium for the poor is paid by the central and local government for short as well as long acting and permanent methods, unlike in Nepal (Lamichhane, 2017) or Madhya Pradesh (Sahasrabuddhe, Kori, Arora & Bute, 2018) where family planning services are more accessible to the rich than to low-income women.…”
Section: Discussionmentioning
confidence: 99%